Giorgos Antoniou and A. Dirk Moses, eds., The Holocaust in Greece - Doxiadis, Evdoxios (Historein, 2021)
Review of Giorgos Antoniou and A. Dirk Moses, eds. The Holocaust in Greece. Cambridge: Cambridge University Press, 2018. xv + 378 pp.